PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR IPA PADA SISWA KELAS IV SD INPRES 2 PARIGIMPUU - Ristina, Ristina; Bustamin, Bustamin; Tureni, Dewi (Jurnal Kreatif Tadulako Online, 2018)
The problem of the research was that the learning outcomen on natural science subject was still low caused by the lack of variation method in the teaching learning process. I general, the teaching learning model was still dominated by speech method, asking question, and assignment method mode the student passive in the classroom. The goal of the research was to improve studentâs learning outcomes through applying STAD cooperative learning type on natural science subject of the grade IV SD Impres 2 Parigimpuu. This research wa classroom action research (CAR) consisted of two cycles. Each cycles consisting of four stages namely: Planning, action , observation and reflection. The results of the research showed that there is an increase from cycle I to cycle II by using STAD cooprative learning type. The test results on cycle I was obtained classsical mastery 58.3 %. The classical achievement on cycle I was 64.88 %. The result on cycle II was obtained classical mastery 91.6 %. The classical achievement on cycle II was 80.25 % The results of the research showed that there is an increase on natural science lerning outcomes. It can be concluded that the learning outcomesÂ on natural science subject of the grade IV studentâs at SDN inpres 2 parigimpuu can be increased through STAD cooperative lerning type. Keywords: Natural Science Learning Outcomes, STAD Cooperative LearningÂ Â Type Model.